VASCULAR MECHANISMS IN THE FORMATION OF GENDER DIFFERENCES IN THE PROTECTIVE EFFECT OF GLUCOSAMINE IN EXPERIMENTAL COLD INJURY - Yuhimchuk, A.V.; Voloshchuk, N.I.; Штриголь, С.Ю.; Nefodov, O.O.; Piliponova, V.V.; Oliinyk, Yu.M.; Tepla, A.M.; Nefodova, O.O. (World of Medicine and Biology, 2023)
The purpose of the study was to assess sex-specific changes in the production of vasoactive molecules during experimental acute cold injury and to investigate endotheliotropic mechanisms that ensure the formation of the body's sex-determining response to the frigoprotective effect of glucosamine. Changes in the production of vasoconstrictor molecules (endothelin-1, adhesion molecules of cranial cellin-1 and vasodilating molecules (H2S, NO) and markers of oxidative stress (nicotinamide adenine dinucleotide phosphate oxidase, superoxide dismutase) in rats of different sexes and the effect on these parameters of prophylactic and therapeutic administration of glucosamine (50 mg/kg intragastrically) were studied on the model of acute cold injury. It was established that acute cold injury causes an increase in the activity of nicotinamide adenine dinucleotide phosphate oxidase, a decrease in the activity of superoxide dismutase in animals of both sexes, an increase in the content of vasoconstrictors and a decrease in the production of vasodilating molecules, to a greater extent in male animals. The endothelial dysfunction degree and oxidative stress's expressiveness in females were statistically lower. Therapeutic and prophylactic administration of glucosamine reduces the severity of pathological changes in the body of animals caused by acute cold injury to a greater extent in male rats. The degree of expressiveness of sex differences in the indicators studied remains. However, the difference in indicators between animals of different sexes decreases.
Keywords: cold injury; gender differences; rats; glucosamine; vasoactive molecules; hydrogen sulfide; nitrogen monoxide; oxidative stress